Democracy is Power: Rebuilding Unions from the Bottom Up - Roberts, Christopher (Labour / Le Travail, 1999)
The article reviews the book, "Democracy is Power: Rebuilding Unions from the Bottom Up ," by Mike Parker and Martha Gmelle.